Exercise during cardiac catheterization distinguishes between pulmonary and left ventricular causes of dyspnea in systemic sclerosis patients. (10th August 2012) - Hager, W. David; Collins, Irina; Tate, Janet P.; Azrin, Michael; Foley, Raymond; Lakshminarayanan, Santha; Rothfield, Naomi F.
Abstract Objective The cause for shortness of breath among systemic sclerosis (SSc) patients is often lacking. We sought to characterize the hemodynamics of these patients by using simple isotonic arm exercise during cardiac catheterization. Methods Catheterization was performed in 173 SSc patients when resting echocardiographic pulmonary systolic pressures were <40 but >40 mmHg post stress. Patients with resting mean pulmonary arterial pressures (mPAP) ≤ 25 and pulmonary arterial wedge pressures (PAWP) ≤ 15 mmHg exercised with 1‐pound hand weights. Normal exercise was defined as a change in mPAP divided by the change in cardiac output (CO) (ΔmPAP/ΔCO) ratio ≤ 2 for patients <50 years (≤3 for >50). An abnormal ΔmPAP/ΔCO ratio, an exercise transpulmonary gradient (TPG) ≥ 15, a PAWP < 20, a ΔTPG > ΔPAWP and a pulmonary vascular resistance (PVR) which increased defined exercise‐induced pulmonary arterial hypertension (EIPAH). An abnormal ΔmPAP/ΔCO ratio, an exercise TPG < 15, a PAWP ≥ 20, a ΔTPG < ΔPAWP and a drop in PVR defined left ventricular diastolic dysfunction (DD). Twelve patients without SSc served as controls. Results Pulmonary pressures increased with exercise in 53 patients. Six had EIPAH and 47 had DD. With exercise, mPAP and PAWP were 20 ± 4 and 13 ± 2 in controls, 36 ± 3 and 12 ± 4 in EIPAH and 34 ± 6 and 26 ± 4 in DD. Control ΔmPAP/ΔCO was 0.8 ± 0.7, 7.5 ± 3.9 in EIPAH and 9.1 ± 7.2 in DD. Rest and exercise TPG was normal for control and DD patients but increased (12 ± 4 to 23 ± 4) in EIPAH (P < 0.0001). PVR decreased in DD but increased in EIPAH with exercise. Conclusions Exercise during catheterization elucidates the pathophysiology of dyspnea and distinguishes EIPAH from the more common DD in SSc patients.